The Influence of Visual Content on Social Media on Generation Z Purchasing Decisions with Brand Engagement as an Intervening Variable - Utari, Dian; Susetyo, Didik; Maulana, Ahmad (Journal of International Conference Proceedings, 2024)
This study aims to analyze the influence of visual content on social media on Generation Z's purchase decisions, with brand engagement as an intervening variable. The population in this study consists of Generation Z in Palembang City, totaling 135 individuals. The sampling technique used in this research is purposive sampling, with criteria for Gen-Z individuals aged 12-27 years, social media users, and those who have made purchases through social media. This study employs a quantitative method with SmartPLS 3.0 as the analysis tool to test the relationships between the proposed variables. The results show that visual content has a significant effect on purchase decisions, both directly and indirectly through brand engagement as an intervening variable. Brand engagement is proven to mediate the relationship between visual content and purchase decisions. These findings highlight the importance of managing creative and relevant visual content for brands to build emotional connections with Generation Z, thus driving purchase decisions. This study offers practical implications for marketers to enhance social media-based marketing strategies to more effectively reach Generation Z.